Enhancing Pancasila Education through Differentiated Learning: The Role of E-Modules Developed with Flip PDF Professional - Septiana Dewi; Alfiandra Alfiandra; Sani Safitri (STAI Hubbulwathan Duri, 2024)
This study addresses the need for high-quality, flexible learning materials in Indonesia’s independent curriculum, focusing on differentiated learning strategies to enhance student motivation in Pancasila Education. The objective is to develop and validate differentiated learning-oriented electronic modules (e-modules) using the professional Flip PDF application to boost student engagement and motivation. The Research and Development (RD) method was applied using the Rowntree model, which includes three phases: planning, development, and evaluation. The study was conducted at SMA Negeri 1 Indralaya Utara, where the e-modules were created to align with differentiated learning principles in content, process, and product design. Validation was conducted through walkthroughs by three experts: a content expert, a media expert, and a linguist. The analysis demonstrated that the developed e-modules were valid, practical, and effective in fostering student motivation. The modules adhered to learner-centered principles, incorporating various elements to meet the needs of differentiated instruction. Experts verified the content quality, usability, and linguistic clarity of the modules. These findings indicate that using differentiated, e-module-based learning materials significantly impacts students' motivation by providing interactive and visually appealing resources aligned with learning objectives. The professional Flip PDF application allowed systematic and engaging content delivery, contributing to improved motivation and learning outcomes. The study successfully developed validated e-modules that enhance student motivation and engagement. Future research could further explore differentiated e-modules across various subjects to support diverse learning needs and optimize educational outcomes.